2020
DOI: 10.3390/genes11080853
|View full text |Cite
|
Sign up to set email alerts
|

Next Generation Sequencing of 134 Children with Autism Spectrum Disorder and Regression

Abstract: Approximately 30% of individuals with autism spectrum disorder (ASD) experience developmental regression, the etiology of which remains largely unknown. We performed a complete literature search and identified 47 genes that had been implicated in such cases. We sequenced these genes in a preselected cohort of 134 individuals with regressive autism. In total, 16 variants in 12 genes with evidence supportive of pathogenicity were identified. They were classified as variants of uncertain significance based on ACM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…Roak et al also found one case of SCN1A missense mutation (p.Pro1894Leu) in 20 patients with ASD, and this mutation may be inherited from its parent (88). A recent study of 134 cases of autism identified 16 variants and 12 genes with evidence of pathogenicity, including three SCN1A mutations (91). In summary, SCN1A is closely related to ASD and has been considered as an ASD candidate gene (6,7,11,89,90) (Figure 3, Table 2).…”
Section: Autism Spectrum Disordermentioning
confidence: 97%
“…Roak et al also found one case of SCN1A missense mutation (p.Pro1894Leu) in 20 patients with ASD, and this mutation may be inherited from its parent (88). A recent study of 134 cases of autism identified 16 variants and 12 genes with evidence of pathogenicity, including three SCN1A mutations (91). In summary, SCN1A is closely related to ASD and has been considered as an ASD candidate gene (6,7,11,89,90) (Figure 3, Table 2).…”
Section: Autism Spectrum Disordermentioning
confidence: 97%
“…Interestingly, rare pathogenic deletions of the GRIN2A gene [ 137 , 138 , 139 , 140 , 141 , 142 ] and heterozygous de novo missense variants [ 143 ] have been implicated in childhood focal epilepsy. Moreover, next-generation sequencing of children with ASD has revealed variants in the GRIN2A gene with evidence that supports ASD pathogenicity [ 144 , 145 ]. Genetic studies have also found a genetic association between ASD and GRIK genes belonging to the kainate family of Glu receptors.…”
Section: The Genetics Of the Glutamatergic System In Asdmentioning
confidence: 99%
“…4 D; Table S4). Some cadherin family members in the TriM-2370 gene set, such as PCDH19 , are known to be high-risk ASD genes (Table S6) that play important roles in brain circuit development [ 35 , 36 ]. Several cadherin family members were also found in the TriM-2370 gene set, including many members of the protocadherin β gene cluster and dachsous cadherin-related 1 ( DCHS1 ), suggesting that these genes also participate in the development and function of brain circuits relevant to ASD.…”
Section: Resultsmentioning
confidence: 99%